Morphological characterization of Peanut (Arachis hypogaea L.) Genotypes - Yami, Abera Seboka (International Journal on Food, Agriculture and Natural Resources, 2025)
AbstractThe current study was done on peanut genotypes including one check.  This study aimed to characterize the morphological variance of genotypes using the Shannon-Weaver diversity index. The experiment was laid out in a simple lattice design. Among the genotypes about (46.94%) had erect growth habits, followed by (34.69%) decumbent-3, while decumbent-2 (12.24%), procumbent-1 (4.02%) and decumbent-1 were the least (2.04%). The genotypes revealed three different branching patterns such as alternate, sequential, and irregular with flowers on the main stem accounting (for 14.29%), (53.06%), and (32.65%) respectively. The majority of genotypes had red (46.96%) seed coat color followed by purple-red (22.45%). Purple, pink, and tan seed colors accounted for (12.24%), (10.20%), and (6.12%) respectively. The white seed coat color was observed for check. Among the studied traits the seed coat color (H'=1.44) had the highest diversity index, followed by leaf color (H'=1.29), pod beak (H'=1.20), and growth habit(H'=1.19), indicating that the presence of high diversity among genotypes for these traits. The diversity in qualitative traits might be good for varietal preference and marketability. This genetic variability can be useful for improvement programs. Therefore, it is recommended that studies should be conducted on molecular characterization besides morphological variabilities.